NeverEndingCycle
  • NeverEndingCycle
Which shows this equation in standard form? 7 – 3(x – y) = 5x + 2 A. 3x – 8y = 5 B. 8x + 3y = 5 C. 8x – 3y = 5 D. 8x – 3y = –5
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
NeverEndingCycle
  • NeverEndingCycle
Thanks! Are you sure?
anonymous
  • anonymous
www.geteasysolution.com/7-3(x-y)=5x+2
anonymous
  • anonymous
It's B

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
I'm 100% sure it's B
NeverEndingCycle
  • NeverEndingCycle
Not d?
anonymous
  • anonymous
No it's B
anonymous
  • anonymous
Look at the website :)
NeverEndingCycle
  • NeverEndingCycle
okay then....If i get this wrong you suck! JK XD
anonymous
  • anonymous
LOL Ok
anonymous
  • anonymous
:p
anonymous
  • anonymous
What if I already suck jk
NeverEndingCycle
  • NeverEndingCycle
XD
anonymous
  • anonymous
hold up... we have - 8x + 3y = -5 now first term must be positive so multiply -1
anonymous
  • anonymous
www.geteasysolution.com/7-3(x-y)=5x+2
anonymous
  • anonymous
check this website
NeverEndingCycle
  • NeverEndingCycle
WBRAAARRRG
anonymous
  • anonymous
What
NeverEndingCycle
  • NeverEndingCycle
WHOS RIGHT THERE ARE TO MANY DIFFERENT ANSWERS!
anonymous
  • anonymous
It's B trust me
NeverEndingCycle
  • NeverEndingCycle
okay then
anonymous
  • anonymous
I know it is
anonymous
  • anonymous
no B is wrong
anonymous
  • anonymous
nope
NeverEndingCycle
  • NeverEndingCycle
STOP CONFUSING ME!! WHAT IS THE ANSWER?
anonymous
  • anonymous
its either C or D.... B to me seems way off
NeverEndingCycle
  • NeverEndingCycle
GHFCCFGVBHJRVHBKCDJCFKVGKB
anonymous
  • anonymous
7-3 (x-y) = 5x+2 *you distribute -3 to (x-y) 7-3x+3y = 5x+2 *then group like terms -3x-5x+3y=2-7 -8x+3y=-5 *then you multiply everything by -1 since u want to have a positive x (-8x+3y=-5)-1 8x-3y=5
NeverEndingCycle
  • NeverEndingCycle
WHICH ONE?!!!!! XD
anonymous
  • anonymous
@Directrix am i correct?
NeverEndingCycle
  • NeverEndingCycle
I hope
anonymous
  • anonymous
7 + -3(x + -1y) = 5x + 2 7 + (x * -3 + -1y * -3) = 5x + 2 7 + (-3x + 3y) = 5x + 2 Reorder the terms: 7 + -3x + 3y = 2 + 5x Solving 7 + -3x + 3y = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + -3x + -5x + 3y = 2 + 5x + -5x Combine like terms: -3x + -5x = -8x 7 + -8x + 3y = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + -8x + 3y = 2 + 0 7 + -8x + 3y = 2 Add '-7' to each side of the equation. 7 + -8x + -7 + 3y = 2 + -7 Reorder the terms: 7 + -7 + -8x + 3y = 2 + -7 Combine like terms: 7 + -7 = 0 0 + -8x + 3y = 2 + -7 -8x + 3y = 2 + -7 Combine like terms: 2 + -7 = -5 -8x + 3y = -5
anonymous
  • anonymous
7 - 3 ( x - y ) = 5x + 2 -7 -7 --------------------- -3x + 3y = 5x -5 -5x -5x --------------- -8x + 3y = -5 next step must multiply by (-1) to get answer
anonymous
  • anonymous
Add '-3y' to each side of the equation. -8x + 3y + -3y = -5 + -3y Combine like terms: 3y + -3y = 0 -8x + 0 = -5 + -3y -8x = -5 + -3y
anonymous
  • anonymous
@NeverEndingCycle when do u know the answer
anonymous
  • anonymous
Ax + By = C ..............Ax term must be positive to be in standard form
anonymous
  • anonymous
when you multiply by (-1) (-8x +3y ) = (-1) -5 you get the answer
anonymous
  • anonymous
but the + stays the same
anonymous
  • anonymous
standard form can have - By or - C just not the first term
anonymous
  • anonymous
idk
anonymous
  • anonymous
wahtever
NeverEndingCycle
  • NeverEndingCycle
im so cunfuzled
NeverEndingCycle
  • NeverEndingCycle
what is the answer?
anonymous
  • anonymous
you had it correct to the point where -Ax and to be in standard form you need to multiply both sides since the equation is already in position of standard form
NeverEndingCycle
  • NeverEndingCycle
so the answer is.......................?
NeverEndingCycle
  • NeverEndingCycle
a b c or d
NeverEndingCycle
  • NeverEndingCycle
?
anonymous
  • anonymous
answer is |dw:1450391323277:dw|
anonymous
  • anonymous
Idk now im confuesed
NeverEndingCycle
  • NeverEndingCycle
me 2
NeverEndingCycle
  • NeverEndingCycle
a b c or d?!
anonymous
  • anonymous
8x - 3y = 5
NeverEndingCycle
  • NeverEndingCycle
k, so, c?
anonymous
  • anonymous
where are you confused?
NeverEndingCycle
  • NeverEndingCycle
is the answer c or not?
anonymous
  • anonymous
when do u know whose correct never ending cycle
anonymous
  • anonymous
yes Never:)
anonymous
  • anonymous
yea
anonymous
  • anonymous
standard form Sydney
NeverEndingCycle
  • NeverEndingCycle
5 minutes-ish
anonymous
  • anonymous
ok well, untill then
NeverEndingCycle
  • NeverEndingCycle
c was right
anonymous
  • anonymous
told ya.. ;p

Looking for something else?

Not the answer you are looking for? Search for more explanations.